Non‐suicidal self‐injury, suicidal thoughts and behaviors in individuals with an eating disorder relative to healthy and psychiatric controls: A systematic review and meta‐analysis. Issue 3 (16th January 2023) - Sohn, Maya N.; Dimitropoulos, Gina; Ramirez, Ana; McPherson, Claire; Anderson, Alida; Munir, Amlish; Patten, Scott B.; McGirr, Alexander; Devoe, Daniel J.
Abstract: Objective: Eating disorders (ED) may be associated with an increased prevalence of non‐suicidal self‐injury (NSSI) and suicidal thoughts and behaviors (STBs) relative to healthy (HC) and psychiatric (PC) controls. However, precise estimates of differences in prevalence between individuals with EDs and controls are unclear. We compared the prevalence of NSSI, suicidal ideation (SI), suicide attempts (SA), and deaths by suicide in controls and individuals with EDs. Method: We searched MEDLINE, PsycINFO, EMBASE, and CINAHL for peer‐reviewed publications reporting the prevalence of NSSI and/or STBs in EDs and HC or PC group (PROSPERO: CRD42021286754). A series of random‐effects meta‐analyses were conducted to estimate pooled odds ratios (ORs) for NSSI, SI, SA, and death by suicide in EDs. Results: Across 32 studies, individuals with an ED had a significantly increased prevalence of NSSI (HC: OR = 6.85 [95% CI: 3.60, 13.04]; PC: OR = 2.74 [95% CI: 1.49, 5.06]), SI (HC: OR = 3.63 [95% CI: 2.43, 5.41]; PC: OR = 3.10 [95% CI: 2.01, 4.78]), and SA (HC: OR = 5.16 [95% CI: 4.27, 6.24]; PC: OR = 1.37 [95% CI: 0.37, 4.99]) relative to HC and PC groups. A 2.93‐times increased odd of death by suicide did not achieve statistical significance. There was a high‐level of heterogeneity between studies. Discussion: Our findings indicate that ED populations have an increased prevalence of NSSI, SI, and SA but not death by suicide compared to controls and emphasize the need for effective clinical strategies to address these behaviors in ED populations. Public Significance: This review provides evidence for an increased prevalence of non‐suicidal self‐injury, suicidal ideation, and suicide attempts in populations with eating disorders compared to controls. Our findings emphasize the need for effective clinical strategies to address these behaviors in patients with eating disorders.